2020
DOI: 10.3389/fmed.2020.00399
|View full text |Cite
|
Sign up to set email alerts
|

False Positive COVID-19 Antibody Test in a Case of Granulomatosis With Polyangiitis

Abstract: Collateral damage due to 2019 novel coronavirus disease (COVID-19) represents an emerging issue. Symptoms of COVID-19 are not disease-specific. Differential diagnosis is challenging and the exclusion of other life-threatening diseases has major caveats. In the era of this pandemic, diagnosis of other life-threatening diseases might delay treatment. The Food and Drug Administration has recently authorized the first antibodybased test for COVID-19; however, RT-PCR of nasopharyngeal or oropharyngeal swabs remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 10 publications
1
19
2
Order By: Relevance
“…8 Another case report described a patient diagnosed with GPA with positive COVID-19 IgM and negative PCR test. 9 However, in our case, GPA developed 4 weeks after true COVID-19 infection confirmed by positive SARS-CoV-2 PCR test. Treatment of GPA involves a multidisciplinary approach and usually includes corticosteroids, rituximab or cyclophosphamide.…”
Section: Discussioncontrasting
confidence: 47%
“…8 Another case report described a patient diagnosed with GPA with positive COVID-19 IgM and negative PCR test. 9 However, in our case, GPA developed 4 weeks after true COVID-19 infection confirmed by positive SARS-CoV-2 PCR test. Treatment of GPA involves a multidisciplinary approach and usually includes corticosteroids, rituximab or cyclophosphamide.…”
Section: Discussioncontrasting
confidence: 47%
“…Later on in the hospitalization, nasal RT-PCR SARS-COV 2 test was positive, and COVID-19 pneumonia soon emerged. We found only one report of false-positive SARS COV 2 RT-PCR test in a patient with AAV, potentially due to cross-reactivity [22]. This was not the case with our patient because a positive RT PCR test was confirmed twice and the disease progressed with worsening of the clinical and radiological features.…”
Section: Discussioncontrasting
confidence: 51%
“…Furthermore, a review of 8,136 pooled specimens showed RT-PCR positivity using nasopharyngeal swabs to be a mere 45.5% (compared to bronchoalveolar lavage with 91.8%) [ 6 ]. Our patient showed positive IgM antibodies to COVID-19, owing to possible recent infection, although there has been a report of cross-reactivity to COVID-19 IgM serological testing in GPA [ 7 ]. We are hesitant to conclude this case as a false-positive, rather we hypothesize patient's delayed presentation and low-yield specimen for PCR testing may have missed an active or recent COVID-19 infection (as illustrated in Figure 1 ).…”
Section: Discussionmentioning
confidence: 79%